Gut Microbiotic Features Aiding the Diagnosis of Acute Ischemic Stroke - Xiang, Lei; Lou, Yanfeng; Liu, Lingyu; Liu, Yuanling; Zhang, Weizheng; Deng, Jianxin; Guan, Yubin; She, Miaoqin; You, Xinchao; Liu, Minqi; Li, Hongwei; Xu, Xiaosong; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Increasing evidence suggests that features of the gut microbiota correlate with ischemic stroke. However, the specific characteristics of the gut microbiota in patients suffering different types of ischemic stroke, or recovering from such strokes, have rarely been studied, and potential microbiotic predictors of different types of stroke have seldom been analyzed. We subjected fecal specimens from patients with lacunar or non-lacunar acute ischemic infarctions, and those recovering from such strokes, to bacterial 16S rRNA sequencing and compared the results to those of healthy volunteers. We identified microbial markers of different types of ischemic stroke and verified that these were of diagnostic utility. Patients with two types of ischemic stroke, and those recovering from ischemic stroke, exhibited significant shifts in microbiotic diversities compared to healthy subjects. Cluster of Orthologous Groups of Proteins (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses revealed reduced metabolic and transport-related pathway activities in ischemic stroke patients. We performed fivefold cross-validation using a Random Forest model to identify two optimal bacterial species (operational taxonomic units; OTUs) serving as markers of lacunar infarction; these were Lachnospiraceae (OTU_45) and Bacteroides (OTU_4), and the areas under the receiver operating characteristic curves (AUCs under the ROCs) were 0.881 and 0.872 respectively. In terms of non-lacunar acute ischemic infarction detection, the two optimal species were Bilophila (OTU_330) and Lachnospiraceae (OTU_338); the AUCs under the ROCs were 0.985 and 0.929 respectively. In post-ischemic stroke patients, the three optimal species were Pseudomonas (OTU_35), Sphingomonadaceae (OTU_303), and Akkermansia (OTU_9); the AUCs under the ROCs were 1, 0.897, and 0.846 respectively. Notably, the gut microbial markers were of considerable value for utility when diagnosing lacunar infarction, non-lacunar acute ischemic infarction, and post-ischemic stroke. This study is the first to characterize the gut microbiotic profiles of patients with lacunar or non-lacunar, acute ischemic strokes, and those recovering from stroke, and to identify microbiotic predictors of such strokes.